2018
DOI: 10.1038/s41388-018-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation process driven by TGF-beta signaling enhances stem cell properties in human colorectal cancer

Abstract: Cancer stem cells (CSCs) possess the capacity for self-renewal and the potential to differentiate into non-CSCs. The recent discoveries of dynamic equilibrium between CSCs and non-CSCs revealed the significance of acquiring CSC-like properties in non-CSCs as an important process in progression of cancer. The mechanism underlying acquisition of CSC-like properties has mainly been investigated in the context of epithelial-mesenchymal transition. Here, we demonstrate the dedifferentiation process may be an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 53 publications
3
82
0
Order By: Relevance
“…One study also showed that E. faecalis , which can cause colitis after infection, can express TGF‐β in the intestinal epithelial cells of wild‐type mice, thereby activating the Smad signaling pathway . In this process, the dedifferentiation of TGF‐β signal transduction enhances the stem cell characteristics of CRC, thereby promoting its occurrence . This is associated with the deletion of the expression of the TLR2 protein and the inhibition of NF‐κB‐dependent pro‐inflammatory gene expression (Fig.…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…One study also showed that E. faecalis , which can cause colitis after infection, can express TGF‐β in the intestinal epithelial cells of wild‐type mice, thereby activating the Smad signaling pathway . In this process, the dedifferentiation of TGF‐β signal transduction enhances the stem cell characteristics of CRC, thereby promoting its occurrence . This is associated with the deletion of the expression of the TLR2 protein and the inhibition of NF‐κB‐dependent pro‐inflammatory gene expression (Fig.…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 93%
“…54 In this process, the dedifferentiation of TGF-β signal transduction enhances the stem cell characteristics of CRC, thereby promoting its occurrence. 55 This is associated with the deletion of the expression of the TLR2 protein and the inhibition of NF-κB-dependent pro-inflammatory gene expression 54 (Fig. 3).…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 99%
“…TWIST1 and SNAI1 (Snail) are master regulators of EMT and the key genes for inducing dedifferentiation of non-CSCs toward a CSC-like state (Batlle & Clevers, 2017;Nakano et al, 2018). TWIST1 mediates this process in a mechanism dependent or independent on EMT (Nakano et al, 2018). ZEB1 is another key regulator of the EMT that its activation by transforming growth factor-β (TGF-β) in non-CSCs could switch them to the CSC state (Chaffer et al, 2013).…”
Section: Plasticity Of Cscs (Stemness Differentiation and Dediffementioning
confidence: 99%
“…Therefore, Lgr5 + CD44 + EpCAM + cells from DLD-1, and seven tissue samples (patient #1, 3,4,6,8,11,12) sorted by flow cytometry were used for further study. Our data showed that the level of KLF4 expression was significantly higher in Lgr5 + CD44 + EpCAM + cells than those of Lgr5 − CD44 − EpCAM − cells ( Figure S1A).…”
Section: Expression Of Klf4 In Lgr5 + Cd44 + Epcam + Colorectal Cscsmentioning
confidence: 99%